Childhood maltreatment moderates the relationship between emotion recognition and maternal sensitive behaviors. (April 2020) - Bérubé, Annie; Blais, Caroline; Fournier, Amélie; Turgeon, Jessica; Forget, Hélène; Coutu, Sylvain; Dubeau, Diane
Abstract: Background: Sensitivity is defined as parents ability to perceive, react and respond to children signals. Having a history of childhood maltreatment changes the way adults perceive visual emotions. These perceptual characteristics could have important consequences on how these parents respond to their children. Objective: The current study examines how a history of childhood maltreatment moderates the relationship between maternal emotion recognition in child faces and sensitive behaviors toward their child during free-play and a structured task. Participants and Setting: Participants included 58 mothers and their children aged between 2 and 5 years. Methods: Mothers were exposed to a set of photographs of child faces showing morphed images of the six basic emotional expressions. Mother-child interactions were then coded for sensitive behaviors. Mothers' history of childhood maltreatment was assessed using the Childhood Trauma Questionnaire. Results: Maltreatment severity was related to poorer abilities in emotion recognition. However, the association between emotion recognition and sensitive behavior was moderate by history of childhood maltreatment. For mothers exposed to a severe form of childhood maltreatment, a better emotion recognition was related to less sensitive behaviors toward the child, both during free-play and the structured task. Conclusion: This relationship is unique to these mothers and is inconsistent with Ainsworth's definition of sensitivity. These results have important implications as they suggest mothers with a history of severe maltreatment would need tailored interventions which take into account their particular reactions to children's emotions.